IMPLEMENTASI ASAS-ASAS PERIKATAN ISLAM TERHADAP KERJASAMA PEMBAGIAN HASIL BUAH JERUK - Oktaviani, Miralis; Yazwardi, Yazwardi; Napisah, Napisah (Program Studi Muamalah Fakultas Syariah dan Hukum, 2024)
Many people use Islamic law as a basis for making agreements, but not a few also do not understand the nature of Islamic law itself, they have only a little supply, Islam is a religion that rahmatanlil'alamin means a religion that is a mercy for the universe. Basically, the scope of human life in this world depends on two kinds of relationships, namely the relationship to God Almighty and the relationship with humans and the surrounding nature. Islamic law itself has laid down some of the foundations of alliances that are influential on the implementation of alliances implemented by interested parties. If these principles are not met in implementing the alliance, then it will result in the annulment or invalidity of the alliance made, so as not to the detriment of each other the parties. In line with the problems to be discussed, then in this case using the type of Field (Field Research) is to collect data directly at the research location or face to face directly to the research object to obtain information that will be needed in the preparation of this Script. Based on the results of this research it can be concluded that in the agreement the system works together, and for their own benefit the parties agreed to divide it evenly, namely 50% for the first party and another 50% for the second party. Application, the Principles of the Islamic Alliance have not been applied well by the parties, such as the example of dishonesty during the distribution of citrus fruits and there are still many very important Principles that have not been applied by the parties who made the agreement such as written principles and other principles.